Origin, structural geometry, and development of a giant coherent slide: The South Makassar Strait mass transport complex - Cipi Armandita (2018)
© 2015 Geological Society of America. The South Makassar Strait mass transport complex (MTC) covers an area of at least 9000 km2 and has a total volume of 2438 km3. It is composed of a shale-dominated sedimentary unit with high water content. Seismic reflection data across the South Makassar Strait MTC show that it displays relatively coherent internal sedimentary stratigraphy that in the toe region is deformed into welldefined thrust-related structures (imbricates, ramps and flats, fault bend folds). It is one of the largest known coherent MTCs. The bowl-shaped central core region is as much as 1.7 km thick, and is confined to the west and east by 355° and 325° trending (respectively) lateral ramps in the upper slope area that pass via oblique ramps into a northeastsouthwest- trending frontal ramp area. The core area passes via the lateral, oblique, and frontal ramps into an extensive, thin (tens of meters thick) region of the MTC (the lateral and frontal apron areas) that are internally deformed by thrusts, normal faults, and thrust faults reactivated as normal faults. The MTC anatomy can be divided into extension headwall, translational, toe, flank, lateral apron, and frontal apron domains. The headwall region is located in the upper slope area of the Paternoster platform; the main body of the slide is in the deep-water region of the Makassar Strait. The complex is interpreted to be triggered by uplift of the platform area (accompanied by inversion), and/or basin subsidence, which caused seaward rotation of ~2° of the Paternoster platform in the Pliocene. Variable uplift promoted sliding dominantly from the eastern and western margins of the headwall. The internal fault patterns of the MTC show that extension in the upper slope to lower slope in the core area changes downslope to compressional structures in the toe domain and apron. Later extensional collapse of parts of the compressional toe area occurred with negative inversion on some faults. The coherent internal stratigraphy, and evidence for multiphase extension in the eastern headwall area, suggests that the ~6-7 km of shortening in the toe region of the MTC occurred at a slow strain rate. Therefore, this type of MTC does not have the potential to generate tsunamis.